Incorporating shortseason legumes and green manure crops into maizebased systems in the moist Guinea savanna of West Africa - Franke, A.; Schulz, S.; Oyewole, B.; Bako, S. (Cambridge University Press, 2004)
A three-year trial was conducted on a degraded soil in the moist Guinea savanna of northern Nigeria to assess the possibility of improving productivity and economic viability of maize-based systems by incorporating short-season legumes and green manure crops into the cropping pattern. Treatments included double cropping legume-maize systems, full-season sole maize receiving various amounts of nitrogen, green manure crop mucuna (Mucuna pruriens var. utilis) followed by sole maize and a legume-maize system receiving additional rice mill waste. In comparison with full-season maize, the use of early-season cowpea followed by maize improved productivity as well as economic returns of the cropping system, while the use of mucuna, grown as an early-season crop or full-season crop, resulted in poor overall productivity of the system. The addition of rice mill waste as a soil amendment in cowpea–maize systems stimulated maize yields and rice mill waste can form a cheap source of organic inputs for farmers living nearby rice mills. Given the limited growing season of the northern Guinea savanna, it is concluded that timing of field operations is crucial for the successful application of double cropping systems. In addition, high labour requirements are a serious constraint for wide-scale adoption of double cropping systems by small-scale farmers, stressing the need to reduce soil cultivation operations, for example by maintaining a uniform ridge distance for all crops in the rotation.